Role of Reference Librarian in Public Relations Activity Role of Reference Librarian in Public Relations Activity in University Library - Rikarda Ratih Saptaastuti (Pustabiblia: Journal of Library and Information Science, 2017)
The library cannot achieve its goals without cooperation with the internal and external public. Therefore, libraries need PR (public relations) in their efforts to achieve their goals. The activity of the university library is directly or indirectly related with the PR activity since it is the part of PR activities to promote the image and the use of the library. The implementation of public relations activities in libraries has actually been performed by reference librarians. Reference librarians can use a variety of printed and online media, or convey information directly related to library services to users. With the recent development of information technology, using online search tools to seek information is more preferable by users than asking the reference librarian. Though online information tracking tool to organize information is more sophisti- cated presenting for users, users will still need libraries and referral services to find relevant information, as there are things that are not provided by online services such as selection, organization, provision of access, interpretation of relevant information, which can only be done by reference librarians. Reference librarians perform their duties by serving users in providing answers to questions or guiding users, and by creating awareness that the services provided by the library help promote maximum utilization of the library. PR officers through reference librarians attempt to attract the users’ attention through the provision and dissemination of information, and to serve as well as a liaison between the libraries with the users. PR becomes a necessity in libraries as PR activities will drive library function effectively and help promote library services more optimally.